Domain specific functional requirements of ERP systems for the agri-food chain - Herdon, Miklos; Füzesi, István; Rózsa, Tünde (Acta Agraria Kaposváriensis, 2006)
Before introduction of an information system the most important aspect in selection is the functionality of system. In depends that what kind of information and economics process are assisted in chosen information system, we can talk about different type of information systems. This types of systems belong to different historical times. This article analyzes functionality of information system in food industry, in consideration of supply chain and food safety.
Keywords: information systems; evaluation; evaluation methods